How Epistemic Beliefs Shape Physics Self-Efficacy among Pre-service Science Teachers: The Mediating Role of Self-Regulative Behavior - Fulminar, Louie Paul (Schrödinger: Journal of Physics Education, 2026)
Purpose of the study: This study aimed to investigate whether self-regulative behavior mediates the relationship between epistemic beliefs and physics self-efficacy among pre-service science teachers. Methodology: This study employed a correlational research design wherein a survey was conducted with 261 randomly selected Bachelor of Secondary Education major in Science students in a Philippine higher education institution. Analysis was conducted using Hayes’ PROCESS macro version 4.2 in SPSS, applying bootstrapping procedures to test indirect effects. Main Findings: Results revealed that self-regulative behavior partially mediates the relationship between epistemic beliefs and physics self-efficacy. The direct effect of epistemic beliefs on physics self-efficacy decreased but remained significant (B = 0.177, Boot SE = 0.079, 95% Boot CI [0.027, 0.335]), representing 48% of the total effect. The indirect effect through self-regulative behavior was also significant (B = 0.191, Boot SE = 0.040, 95% Boot CI [0.117, 0.273]), accounting for 52% of the total effect. Novelty/Originality of this study: This study highlights self-regulative behavior as a mediator in physics self-efficacy, offering new insight into how epistemic beliefs translate into confidence. It informs teacher education by emphasizing the integration of epistemological sophistication and regulation strategies to enhance pre-service teachers’ learning and teaching preparedness.